Comparisons of Elasticity Moduli of Different Specimens Made Through Three Dimensional Printing - Ahmed, M.; Islam, M Aminul; Vanhoose, J.; Rahman, M. (2017)
The advent of three-dimensional (3D) printing technology changed modern manufacturing in many different ways. 3D printed parts based on the fused deposition method (FDM) are widely used in many different applications. However, parts made from polymer-based filaments are generally not strong enough to meet engineering needs. Today, plastic filaments reinforced with carbon fibers and carbon nanotubes are also available in the market to be used in FDM-based 3D printers. Whether reinforcing regular plastic filaments with carbon fibers or carbon nanotubes improves mechanical properties of 3D printed parts is a big question. The purpose of the current research is to investigate the mechanical properties of 3D-printed specimens from these composite filaments. Tensile testing was carried out on a set of 3D-printed specimens made from ABS, PLA, carbon fiber-reinforced ABS, carbon fiber-reinforced PLA, and nanotube-reinforced ABS filaments. The specimens for testing were designed according to ASTM guidelines. A small tensile testing machine with a real-time data acquisition system was used for testing and collecting data. For each material, the test was carried out multiple times. The results showed that for a given material the standard deviation is very small indicating high repeatability of the data. Statistical analysis using Student-t distribution shows that the modulus of elasticity for the reinforced filaments was higher than their nonreinforced counterparts.